Current status of the laboratory diagnosis of anthrax: detection and identification of Bacillus anthracis - L. V. Sayapina; R. N. Lobach; V. P. Bondarev; N. F. Nikityuk (Биопрепараты: Профилактика, диагностика, лечение)
The present article summarizes the materials from literary sources dedicated to the issues of laboratory diagnosis of anthrax. It shows the priority of the development of new methods for the elaboration of highly sensitive test systems and preparations designed for the detection and identification of anthrax bacteria. It outlines the role of express-diagnostics of infectious diseases, which is very important when investigating bioterrorism cases, outbreaks and sporadic cases in humans and animals. Providing with the analysis of different methods for detection of anthrax, the article at the same time focuses on modern molecular diagnostic technologies. It is shown that the basic parameters of diagnostic test systems are sensitivity, specificity and reproducibility of the results. The article presents data on the development of culture media for isolation and identification of anthrax, as well as the possibility of using anthrax bacteriophage for phage-based indication and identification of bacteria.